Health Learning Management at Sam Ratulangi Hospital, Minahasa Regency - Paturusi, Achmad; Pandeleke, Tony; Piri, Nofri Iwan; Mamuaja, Prycilia Pingkan (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
This study aimed to analyse and describe Health Learning Management in health centres in Minahasa Regency. Health learning management is a form of learning management that focuses on nursing services in their role as educators, where nurses are responsible for non-medical as well as medical matters, namely educating patients and patients' families through health learning. The results showed that health learning management was carried out by H. Adam Malik Hospital Manado, which is the current research site. The stages of health learning are through planning that is carried out by nurses before carrying out nursing tasks, implementation of learning that refers to the planning that has been done, and evaluation of learning by monitoring the implementation of health learning management. RSUD Samratulangi Hospital has sufficient resources both human resources to implement Health Learning Management as stated in the guidebook and has been planned in accordance with the medical duties of nurses in nursing care, however, there are still weaknesses and shortcomings that need to be addressed, especially by the hospital and especially the hospital director, so that Health Learning Management can be further optimised to support improving the quality of health services.